Religion and spirituality in specific clinical situations in medical practice: a cross-sectional comparative study between patients and doctors in a tertiary care hospital in Malaysia - Rathor, Mohammad Yousuf; Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Mohd Shah, Azarisman Shah (Islamic World Academy of Sciences, 2009)
In recent years there has been growing awareness regarding the role of religion and spirituality (R/S) in the practice of clinical medicine. We aim to assess the beliefs and practises of physicians regarding the role of R/S in clinical practice. Concomitantly, we aim to assess the beliefs of our patients and whether they like to address such issues. Questionnaire based cross sectional study among hospitalized patients and their treating doctors. The majority of patients were male (62.9%), Malay Muslims (75.4%) and had primary (32.5%) or secondary (48.6%) education. Nearly all patients and doctors believed in the existence of God and life after death. Although significant majority of both patients and physicians agreed that religious involvement is associated with improved health, only half of doctors discussed such issues in clinical situations. Three quarters of patients noticed an increase in faith due to illness and similar proportion wanted a religious counsellor to help them rather than a psychiatrist. Only a quarter of physicians agreed with euthanasia, 68% with use of placebo and just 10% with false hope of cure, while among patients only 6.4% agreed with euthanasia and 92% had a hope of cure. Religion is important to many patients and doctors, but more than half doctors ignore it in their clinical practice, a discrepancy between beliefs and behaviour. In conclusion, religion deserves greater attention in the practice of medicine. Key Words: Spirituality, medicine and religion, euthanasia.